Endothelium-Induced Proliferation and Electrophysiological Differentiation of Human Embryonic Stem Cell-Derived Neuronal Precursors - Lai, Bin (Mary Ann Liebert, Inc., 2008)
Neurogenesis occurs in a stem cell niche in which vascular elements, including endothelial cells (ECs), are thought to play an important role. Using co-culture experiments, we investigated the effect of ECs on proliferation and functional neuronal differentiation of human embryonic stem (ES) cell-derived neuronal precursor cells (NPCs). NPCs were cultured for 5 days in medium containing fibroblast growth factor-2 (FGF-2), with or without ECs. FGF-2 and ECs were then removed, and NPCs were maintained in culture for additional periods. Compared to control NPC cultures, EC-treated NPC cultures showed increased cell proliferation at short intervals (5 days) after withdrawal of FGF-2 and larger tetrodotoxin-sensitive inward membrane currents at longer intervals (10–14 days), but a similar pattern of development of neuronal differentiation markers. The effects of ECs appeared to result from the release of soluble factors rather than from cell contact, because they were observed despite the physical separation of NPCs from ECs by a cell-impermeable membrane. These findings indicate that ECs can regulate the proliferation and electrophysiological neuronal differentiation of human NPCs.